DIALECTIC OF THEOLOGY AND MYSTICISM IN ISLAM: : A STUDY OF IBN TAYMIYYA - Sirait, Sangkot (Sekolah Tinggi Agama Islam (STAI) Sadra, 2016)
Islamic theologians and sufi orders are rarely considered to have totally different ways of of discovering the truth of God. In the view of Ibn Taymiyya, on the contrary, Islamic theology and mysticism, both together strive to deliver people to understand the existence of God so they are, accordingly, willing to do good and leave the bad. This what will bring into the perfection of human soul. What makes it different is that Islamic theology (kalÄm) is more theoretical, while mysticism is more practical. Islamic theology as a theoretical mean leads man to the logical belief. Yet, the realization of this logical belief will practically be appeared when it was charged by Sufism. Yet, Ibn Taymiyya denies such concepts as â€œunion with Godâ€ as the highest goal of human life. Absorption into the God and contemplation into the highest Reality should be realized in terms of sharÄ«â€˜a. For him, the supreme absorption is the absorption in worshiping (â€˜ibÄda) God.